Analyzing the mechanisms that facilitate the subtype-specific assembly of γ-aminobutyric acid type A receptors - Choi, Catherine; Smalley, Joshua L.; Lemons, Abigail H. S.; Ren, Qiu; Bope, Christopher E.; Dengler, Jake S.; Davies, Paul A.; Moss, Stephen J. (Frontiers in Molecular Neuroscience, 2022)
Impaired inhibitory signaling underlies the pathophysiology of many neuropsychiatric and neurodevelopmental disorders including autism spectrum disorders and epilepsy. Neuronal inhibition is regulated by synaptic and extrasynaptic γ-aminobutyric acid type A receptors (GABAARs), which mediate phasic and tonic inhibition, respectively. These two GABAAR subtypes differ in their function, ligand sensitivity, and physiological properties. Importantly, they contain different α subunit isoforms: synaptic GABAARs contain the α1-3 subunits whereas extrasynaptic GABAARs contain the α4-6 subunits. While the subunit composition is critical for the distinct roles of synaptic and extrasynaptic GABAAR subtypes in inhibition, the molecular mechanism of the subtype-specific assembly has not been elucidated. To address this issue, we purified endogenous α1- and α4-containing GABAARs from adult murine forebrains and examined their subunit composition and interacting proteins using liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) and quantitative analysis. We found that the α1 and α4 subunits form separate populations of GABAARs and interact with distinct sets of binding proteins. We also discovered that the β3 subunit, which co-purifies with both the α1 and α4 subunits, has different levels of phosphorylation on serines 408 and 409 (S408/9) between the two receptor subtypes. To understand the role S408/9 plays in the assembly of α1- and α4-containing GABAARs, we examined the effects of S408/9A (alanine) knock-in mutation on the subunit composition of the two receptor subtypes using LC-MS/MS and quantitative analysis. We discovered that the S408/9A mutation results in the formation of novel α1α4-containing GABAARs. Moreover, in S408/9A mutants, the plasma membrane expression of the α4 subunit is increased whereas its retention in the endoplasmic reticulum is reduced. These findings suggest that S408/9 play a critical role in determining the subtype-specific assembly of GABAARs, and thus the efficacy of neuronal inhibition. Data are available via ProteomeXchange with identifier PXD03629.